2014
DOI: 10.1007/s00253-014-5690-y
|View full text |Cite
|
Sign up to set email alerts
|

Cerato-platanins: a fungal protein family with intriguing properties and application potential

Abstract: Cerato-platanin proteins are small, secreted proteins with four conserved cysteines that are abundantly produced by filamentous fungi with all types of lifestyles. These proteins appear to be readily recognized by other organisms and are therefore important factors in interactions of fungi with other organisms, e.g. by stimulating the induction of defence responses in plants. However, it is not known yet whether the main function of cerato-platanin proteins is associated with these fungal interactions or rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 35 publications
5
72
0
Order By: Relevance
“…The biochemical functions of cerato‐platanins remain elusive. De Oliveira and colleagues () showed that they had a structure similar to expansins and barwin‐like endoglucanases, suggesting an activity involved in carbohydrate metabolism (Baccelli et al ., ; Gaderer et al ., ). However, they have no activity against a variety of carbohydrates.…”
Section: Resultsmentioning
confidence: 97%
“…The biochemical functions of cerato‐platanins remain elusive. De Oliveira and colleagues () showed that they had a structure similar to expansins and barwin‐like endoglucanases, suggesting an activity involved in carbohydrate metabolism (Baccelli et al ., ; Gaderer et al ., ). However, they have no activity against a variety of carbohydrates.…”
Section: Resultsmentioning
confidence: 97%
“…These properties and their developmental expression in axenic fruiting bodies suggest a role in FCW remodeling, although antimicrobial activities also have been predicted for certain members (Krizsán et al ., ). Cerato‐platanins represent a similar case (see also above); they are widely expressed in pathogenic fungi–plant interactions (Chen et al ., ; Gaderer et al ., ), fruiting bodies (Gaderer et al ., ; Sipos et al ., ; Krizsán et al ., ) and assays of fungal defense against predators (Plaza et al ., ), and are significantly enriched in Agaricomycetes genomes (Chen et al ., ; Krizsán et al ., ). Thaumatins and cerato‐platanins provide examples of gene families traditionally associated with plant pathogenicity but for which deeper analyses reveal morphogenetic functions, suggesting a link between morphogenesis and pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…Many members that belong to the cerato-platanin family have been characterized from filamentous fungi including M. oryzae and B. cinerea and some of them have shown to trigger immunity in a number of plant species2223. We and others have shown that, transient or stable expression of MoSM1 in Arabidopsis or application of recombinant MoMSP1 in rice activated a series of defense responses, which conferred a broad-spectrum resistance against fungal and bacterial pathogens3242.…”
Section: Discussionmentioning
confidence: 95%
“…The cerato-platanin (CP) family is a newly identified small, secreted and cysteine-rich protein (~150 aa) family from filamentous fungi222324. CP was first identified from the tree pathogen Ceratocystis platani (formerly known as Ceratocystis fimbriata f. sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation